PENGELOLAAN LEMBAGA KURSUS PELATIHAN BORDIR DI KOTA SOLOK (Studi Kasus Pada Lembaga Kursus Pelatihan Bordir Muslimah Group) - Oktarina, Silvi; Ernawati, Ernawati; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The study purpose describes management of the Institute Training Course (ITC) Muslimah Group in terms of: planning and execution of training, training evaluation. The study used qualitative research with case study appoach. Research location took inITC Muslimah Group Solok City. Data type used primary and secondary data. Data collection used the method of observation, interviews, and documentation. Reseach Data were analyzed using data reduction, data presentation, and conclusion. Test validation performed by the observation data by extension, increase persistence, triangulation and auditing. The results of the study consisted of management education, students, personnel, finance, marketing, management of distribution / service alumni, and infrastructure include: (1) Training plan determine by setting training objectives, the organizational structure of managers, instructors and participants, teaching materials, training methods, cost / funding sources, the implementation of training, facilities and infrastructure space, tools and materials are provided, (2) Training implementation apllied in: The beginning stage, filling the participants biodata, the implementation stage include: theory and practice learning, the implementation of the embroidery, learning to embroider, and the evaluation stage (monitoring) with a competency test and follow-up plan (RTL), (3) Evaluation includes evaluation training: instructors, and reception of participants, the training process. Â Â Kata Kunci: Pengelolaan Lembaga Kursus Pelatihan (LKP)